Intra-abdominal Aspergillosis due to Aspergillus fumigatus in a Dog - KALOGIANNI, L; SOUBASIS, N; SARIDOMICHELAKIS, M; VLEMMAS, I; VELEGRAKI, A; PAPAZOGLOU, L; KRITSEPI-KONSTANTINOU, M; RALLIS, T (Journal of the Hellenic Veterinary Medical Society, 2018)
A 3 year-old, spayed female, mixed-breed dog presented with abdominal distension due to a large mass, detected during abdominal palpation and confirmed by abdominal imaging. Cytological examination of the mass was suggestive of pyogranulomatous inflammation. During exploratory laparotomy, extensive peritoneal adhesions and multifocal nodular lesions on the liver, spleen and omentum were revealed. One week later, the dog deteriorated and was euthanized. Numerous firm masses were observed in the liver, spleen, left kidney, stomach, small and large intestine during necropsy. The lungs, heart, and ocular structures were macroscopically normal. Histopathology results (surgery and necropsy) revealed fungal hyphae enclosed in the pyogranulomatous lesions. Polymerase chain reaction (PCR) products showed 100% homology with Aspergillus fumigatus and agar gel double diffusion was positive for IgG antibodies against the same fungus.